Analysis of Factors Affecting the Human Development Index (HDI) in 43 Sub-Saharan African Countries 2018-2022 - Meilita, Fristyan Yuris; Hasmarini, Maulidyah Indira (Jurnal Ekonomi Balance, 2024)
The Human Development Index (HDI) is a crucial metric for assessing the quality of life and welfare in a region. However, Sub-Saharan African countries continue to encounter challenges in improving their HDI. This research aims to analyze the effects of economic growth, population growth, the Corruption Perception Index, and unemployment rates on HDI across 43 Sub-Saharan African nations from 2018 to 2022. The analytical approach employed includes panel data regression with Pooled Least Square (PLS), Fixed Effect Model (FEM), and Random Effect Model (REM). The Chow test and Hausman test are utilized to identify the most suitable estimation model. The findings indicate that the Fixed Effect Model (FEM) is the most appropriate model, demonstrating the significant impact of population growth and the Corruption Perception Index on HDI in these countries. Conversely, economic growth and unemployment rates do not show a significant influence. Among the 43 Sub-Saharan African nations, Mauritius stands out with the highest HDI, while Niger has the lowest.